THE ANALYSIS OF DIVORCING PHENOMENON IN PROBOLINGGO REGENCY (Case Study in Clarak Village, Leces District, Probolinggo Regency) - Jamil Jamil (USRAH: Jurnal Hukum Keluarga Islam, 2020)
This research examines the Phenomenon of Divorce in Probolinggo Community Case Study Clarak Village Leces District Probolinggo Regency. This study aims to determine how the cases of divorce problems in the Probolinggo community, especially in the village of Clarak Leces District. What are the factors and impacts of divorce in the Probolinggo community, Clarak Village, Leces District, Probolinggo. This research uses a qualitative description research method with data collection, interviews, documentation and in a secondary way, which are literature review through books, journals, reports and internet sites related to the research topic as well as important documents, and primarily, are collecting information, either from the community involved in a divorce in Clarak Village or in KUA and others, or from parties and direct opinions from the local community. The results of this study conclude that the Divorce Phenomenon in Clarak Village Community is still considered high, it means that the problem of divorce, has not been resolved optimally, almost every year there are still those who divorce. Divorce problems in Leces, Probolinggo. are caused by several things, among others; Disharmony at home, moral and moral crisis, adultery, strife, infidelity, boredom, early-age marriage and marriage without love. Divorce does not mean that it only involves both partners who are in trouble but their families also feel that they are in trouble, many of the divorced couples do not think about their respective families or do not pay attention to how and what is happening, especially to their children, when the divorce process will occur or has happened, this divorce is usually preceded by these various conflicts.Key Words : Divorce, KUA Clarak, Moral